Question

# Find the square root of $5 - \sqrt {10} - \sqrt {15} + \sqrt 6$

Hint: - Let the square root of the given equation be$\left( {{\text{1 + }}\sqrt a - \sqrt b } \right)$, and also use the property which is ${\left( {a + b - c} \right)^2} = {a^2} + {b^2} + {c^2} + 2ab - 2bc - 2ca$

Given equation
$5 - \sqrt {10} - \sqrt {15} + \sqrt 6$
Square root of given equation is
$\sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 }$
There are four terms in the given equation therefore in the square root of this it has three terms.
So, let ${\text{1 + }}\sqrt a - \sqrt b = \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } ................\left( 1 \right)$
Squaring both sides
${\left( {{\text{1 + }}\sqrt a - \sqrt b } \right)^2} = {\left( {\sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } } \right)^2}$
Now, as we know that ${\left( {a + b - c} \right)^2} = {a^2} + {b^2} + {c^2} + 2ab - 2bc - 2ca$
$\Rightarrow 1 + a + b + 2\sqrt a - 2\sqrt {ab} - 2\sqrt b = 5 - \sqrt {10} - \sqrt {15} + \sqrt 6 \\ \Rightarrow 1 + a + b + 2\sqrt a - 2\sqrt {ab} - 2\sqrt b = 5 + \sqrt 6 - \sqrt {15} - \sqrt {10} \\$
So, on comparing
$1 + a + b = 5{\text{, }}\sqrt a = \dfrac{{\sqrt 6 }}{2},{\text{ }}\sqrt {ab} {\text{ = }}\dfrac{{\sqrt {15} }}{2}{\text{, and }}\sqrt b = \dfrac{{\sqrt {10} }}{2} \\ \sqrt a = \dfrac{{\sqrt 6 }}{2} \Rightarrow a = \dfrac{6}{4} = \dfrac{3}{2} \\ \sqrt b = \dfrac{{\sqrt {10} }}{2} \Rightarrow b = \dfrac{{10}}{4} = \dfrac{5}{2} \\$
From equation (1)
${\text{1 + }}\sqrt a - \sqrt b = \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } \\ \Rightarrow \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } = 1 + \sqrt {\dfrac{3}{2}} - \sqrt {\dfrac{5}{2}} \\$
As we know perfect square root always gives us $\pm$condition
$\Rightarrow \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } = \pm \left( {1 + \sqrt {\dfrac{3}{2}} - \sqrt {\dfrac{5}{2}} } \right)$
So, this is the required square root.

Note: -In such types of questions always assume the required square root as above then take square on both sides and compare its terms and calculate the values of $a$ and $b$ then from the equation which we assumed substitute the values of $a$ and $b$ we will get the required square root.